1999
DOI: 10.1002/(sici)1522-2586(199904)9:4<596::aid-jmri14>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

MRI compatibility and visibility assessment of implantable medical devices

Abstract: We have developed a protocol to evaluate the magnetic resonance (MR) compatibility of implantable medical devices. The testing protocol consists of the evaluation of magnetic field-induced movement, electric current, heating, image distortion, and device operation. In addition, current induction is evaluated with a finite element analysis simulation technique that models the effect of radiofrequency fields on each device. The protocol has been applied to several implantable infusion pumps and neurostimulators … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
48
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 17 publications
1
48
0
Order By: Relevance
“…According to the above-mentioned standard, magnetically induced torque has to be smaller than the product of the maximum device length and device weight, i.e., the mechanical torque T me due to gravity. Several medical products as surgical instruments or prosthetic heart valves have been examined for hazardous torque in the MR environment applying at least the limits in this standard (3)(4)(5)(6)(7)(8)(9)(10)(11)(12).…”
mentioning
confidence: 99%
“…According to the above-mentioned standard, magnetically induced torque has to be smaller than the product of the maximum device length and device weight, i.e., the mechanical torque T me due to gravity. Several medical products as surgical instruments or prosthetic heart valves have been examined for hazardous torque in the MR environment applying at least the limits in this standard (3)(4)(5)(6)(7)(8)(9)(10)(11)(12).…”
mentioning
confidence: 99%
“…Previously performed numerical studies have only focused on the evaluation of the amount of RF energy absorbed by the tissues around different implants (SAR), but not on the device electronics. Schueler et al [2] calculated the magnetic field around an aluminum spheroid implant as well as the eddy currents on this implant surface. Field distribution around this spheroid implant was similar to the results obtained in the present work, but the RF field magnitude was not specified.…”
Section: Discussionmentioning
confidence: 99%
“…It is relatively easy, for example, to demonstrate that heating or induced voltages can occur, but far more difficult to prove that they are not hazardous. Experimental studies have been extensively used to assess the MRI-safety of various active implants (pacemakers [4]- [9], defibrillators [1], [5], neurostimulators [10], [11], and infusion pumps [2], [12], [13]) and this type of investigation is mandatory before the commercialization and marketing of implants as MRI safe. However, experimental tests are only possible at the end of the product development cycle when fully functional implants are available and design change costs are the highest.…”
mentioning
confidence: 99%
“…The stent-graft was suspended by a fine string, attached at the estimated center of mass, to a specially constructed device (a plastic protractor mounted on a wooden stand) and placed at the portal of the magnet bore (15)(16)(17)24,26). The accuracy of this device is Ϯ0.5°.…”
Section: Assessment Of Ferromagnetismmentioning
confidence: 99%
“…Previous studies have shown that MRI is safe if the metallic implant exhibits none, or negligible, ferromagnetism, in the sense that the metallic implant is not affected by the static magnetic field (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). With respect to heating, patients may safely undergo MRI if the metallic implant is not or is only slightly (Յ1.0°C) heated when tested ex vivo (16,(22)(23)(24)(25)(26)(27)(28)(29).…”
mentioning
confidence: 99%